Prevalence of Hypothyroidism in Hemi-thyroidectomy Cases in a Tertiary Care Hospital of Chitwan, Nepal - Bhandari, Chhanya; Paudel, Sanjaya; Sharma, Bibek; Adhikari, Sabin; Upadhyay, Hari Prasad (Journal of Bharatpur Hospital, 2025)
Background Hypothyroidism following hemithyroidectomy surgery has a variable incidence. The purpose of the present study was to determine the prevalence and the risk factors of hypothyroidism following hemithyroidectomy surgery. Methods This analytical cross-sectional study was conducted among euthyroid patients who underwent hemithyroidectomy between August 2024 and April 2025 for benign disease in College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan, Nepal. The prevalence of hypothyroidism (thyroid stimulating hormone (TSH) levels > 4.5 micro-IU/L) was analyzed. Factors like preoperative TSH level and gender associations were evaluated for the development hypothyroidism postoperatively. Data was analyzed using Students t test. p-value<0.05 was considered as statistically significant. Results This study was conducted among 122 patients. All patients were euthyroid preoperatively. They underwent hemithyroidectomy surgery for benign thyroid swelling. The prevalence of Hypothyroidism in Hemi- thyroidectomy cases was 16.39%. Out of which 8 patients (6.55%) developed overt hypothyroidism and 12 patients (9.83%) developed subclinical hypothyroidism. Majority of patients who developed postoperative hypothyroidism were female (90%). Conclusions About one fifth of euthyroid patients who undergo hemithyroidectomy developed hypothyroidism. Majority of postoperative hypothyroid patients were of female gender and with preoperative TSH level more than 2 micro-IU/L. It is concluded that, postoperative hypothyroidism should be considered in female patients with baseline TSH level more than 2 micro-IU/L.